Background of the use of artificial intelligence in university students in the Dominican Republic - Sánchez, Abdali Ysabel; Orgaz Agüera, Francisco; Trinidad Domínguez, María Esther; Domínguez Valerio, Cándida María (LACCEI, 2025)
The paper analyzes the factors that influence the adoption of artificial intelligence (AI) in university students in the Dominican Republic, focusing on knowledge about AI, its perceived usefulness, privacy concerns, current use, and future willingness to use it. Based on surveys of students at the Technological University of Santiago, the study uses the PLS-SEM methodology to evaluate the relationships between these factors. The results reveal that knowledge about AI positively influences their perception of usefulness and frequency of use. Furthermore, perceived usefulness is a key predictor of current use and future intention to use it. Although concerns about privacy and security have a minor effect, it is still significant. It is concluded that training in AI and practical exposure is essential for its integration in higher education, recommending institutional policies that promote its responsible and equitable adoption.